Histological characterization of Sticholecitha serpentis Prudhoe, 1949 (digenea, bieriidae, sticholecithinae), parasite of Bothrops moojeni Hoge, 1966 (serpentes, viperidae) - Silva,TB. (2005)
The aim of this study was to evaluate the morphology of the species Sticholecitha serpentis Prudhoe, 1949 by means of histological procedures. Helminths were previously fixed in Railliet & Henry solution, uncompressed and were included in 2-hydroxyethyl-methacrylate. Longitudinal and transverse serial sections with a 4-mum thickness were performed in a microtome (Leica RM 2165), stained with haematoxylin-eosin and then analyzed in a computerized image analysis system (Qwin Lite 2.5, Leica). Structures of systematic value, such as oral sucker, acetabulum, prepharynx, pharynx, esophagus, intestinal caeca, vitelline glands, ovary, uterus, cirrus pouch and testicles were described. Structures that were poorly visible in total preparations were also observed and described, such as efferent ducts, ejaculatory duct, prostate, seminal vesicle, seminal receptacle, Laurers channel, Mehlis gland, vitelline ducts, metraterm, genital atrium, digestive glands and excretory vesicle. We demonstrated that histological analysis can supply important data regarding the morphological characterization of S. serpentis and will be able to contribute to systematic studies of trematodes.